Using shared digital documents to increase collaboration and engagement - Gregory, Jess L. (Delta Kappa Gamma Bulletin: Collegial Exchange, 2020)
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

COVID-19 elevating the problem of plagiarism: The implied social contract of academic integrity - Gregory, Jess L. (Delta Kappa Gamma Bulletin, 2020)
Keywords: COVID-19; COVID-19 pandemic; EDITORIAL boards; ICELAND; dept.edl; ⛔ No DOI found

Plagiarism as a social contract, a new way to approach plagiarism - Gregory, Jess L. (Journal of Academic Ethics, 2021)
Most cases of plagiarism involve a power differential where not every person has the same ability to enter into a social contract. A social contract requires that each party understands the expectations or norms of the contract, has a voice in setting or changing the norms and has the ability to exit the contract. If those with less power want to gain power then they have to engage in activities bound by norms set by others with little or no ability to exit and no voice. Even if one determines that it is an option to choose a role that requires academic writing, even at the earliest grades, then the social contract demands a shared norm of what constitutes correct behavior. This study reviewed the abstracts of articles indexed in Google Scholar from 1999–2019 through the lens of integrative social contract theory (ISCT) and found, in the case of plagiarism, an existing consensus of correct behavior does not exist. Recommendations for establishing a social contract conclude the article.
Keywords: dept.edl; peer-reviewed

The role of ego threat in professional growth: Fulfilling the ethical intentions of the SEED Model - Gregory, Jess L.; Mebane, Karreem A. (Educational Practice and Theory, 2020)
Schools and education in general have made an implicit and, we would assert, explicit promise to society to educate all the children in their care. Unfortunately, there are achievement gaps that illustrate how schools have broken this promise. Teacher evaluation and other accountability measures have been heralded as the answer to this problem. Educator ego threat impedes the implementation of goal-driven teacher evaluation models and, thus, ethical questions arise. To realize the noble goals of educator evaluation, leaders must attend to ethical concerns and to the human aspects of ego threat.
Keywords: Educational leadership; Ego threat; Goal-setting models; Teacher evaluation; Teacher performance; dept.edl; dept.rec; peer-reviewed

Polish and Indian teachers’ self-efficacy and attitudes towards inclusion of children and youth with disabilities in regular classrooms - Ćwirynkało, Katarzyna; Parchomiuk, Monika; Gregory, Jess; Ravi, Sunitha; Krishnamurthy, Sita (International Journal of Inclusive Education, 2025)
Keywords: Developmental psychology; Inclusion (mineral); Mainstreaming; Mathematics education; Pedagogy; Psychology; Self-efficacy; Social psychology; Sociology; Special education; Teachers; attitudes towards inclusion; dept.edl; inclusion; self-efficacy; students with disabilities

School Leadership for Learning: Learning Theory to Improve Professional Practice - Gregory, Jess L.; Ben-Avie, Michael; Billups, Felice; Grassetti, Mary; Hesser, Tiffany; Lawlor, Jennifer Lynne; Martone, Drey; Maykel, Cheryl; Minkos, Marlena L.; Paslov, Linda; Trombly, Christopher; Tucker, Lauren; et al. (Jess L. Gregory, 2021)
Keywords: Educational leadership; School administrators; Handbooks, manuals, etc; In-service training; School administrators; In-service training; Teachers; dept.edl; dept.sed; faculty_collection